Perancangan ATS Untuk Rumah Walet di Paket 2 TR 23 Desa Banyu Abang - Yudi Chandra (Electrical Network Systems and Sources, 2022)
A Swallow's house is a house that is dedicated as a place for swallows to enter and make nests. The part that can be used by swallows is the swallow's nest. The swallow house itself operates 24 hours. ATS (Automatic Transfer Switch) itself is a system equipment that can regulate the change in the supply of electric power from the main power source from PLN to a backup power source that works automatically by controlling the timing. Therefore, we need a circuit or automatic device that can move the power source from the main source to a backup source or vice versa. By considering the problem points above, an alternative was created to overcome this problem, so a tool called ATS (Automatic Transfer Switch) was created to solve it. In this research, a single-phase ATS will be designed by reducing the number of contactors to get more economical results and easy maintenance. ATS in this study uses a control circuit based on relay and Time Delay Relay (TDR). When the PLN blackout occurs, there is a time delay of 5 seconds before the battery or battery supplies the circuit. This is done to protect the components from damage if PLN occurs for a brief blackout. The outcomes of the ATS design using components such as contactors, relays, TDRs, and inverters. A circuit is formed that can move the power source automatically. This circuit can be applied to cities or other large industries by replacing a backup power source by using an existing power source in the area. The cost of making ATS is quite affordable, ranging from only 2-3 million, and the materials needed to make this ATS are very easy to obtain both through offline and online media, and the price of the materials is very affordable.